Nutritional quality of fruits and vegetables 2009 - Vicente, Ariel Roberto; Crisosto, Carlos H.; Sozzi, Gabriel O.; Manganaris, George A. (My University, 2009)
The nutritional value of fruits and vegetables depends on their composition, which shows a wide range of variation depending on the species, cultivar, and maturity stage. This chapter describes the general characteristics of the components of fruits and vegetables, related to their benefits as food sources. There are two types of acids, namely aliphatic (straight chain) and aromatic acids. The most abundant acids in fruits and vegetables are citric and malic (both aliphatic) acids. However, large amounts of tartaric acid occur in grapes. Malic acid is the major component in oranges and apples. The acid content of fruits and vegetables generally decreases during maturation. Aromatic organic acids occur in several fruits and vegetables, but in very low concentrations. Benzoic acid occurs in cranberries, quinic acid in bananas, and chlorogenic acid in potatoes. In general, vegetables are a richer source of minerals than fruits, but both vegetables and fruits are considered nutrient-dense foods in that they provide substantial amounts of micronutrients, such as minerals and vitamins, but relatively few calories. Minerals have both direct and indirect effects on human health. The direct effects of minerals focus on the consequences of their consumption on human nutrition, while the indirect effects refer to their incidence in fruit and vegetable quality and subsequent consumer acceptance. From a direct nutrition standpoint, potassium has the biggest presence in both fruits and vegetables, but nitrogen and calcium show major impacts on horticultural crop qual
Keywords: Fruits; Foods; Vegetables; Calories; Calcium